2003
DOI: 10.1063/1.1528301
|View full text |Cite
|
Sign up to set email alerts
|

Domain epitaxy: A unified paradigm for thin film growth

Abstract: We present a unified model for thin film epitaxy where single crystal films with small and large lattice misfits are grown by domain matching epitaxy (DME). The DME involves matching of lattice planes between the film and the substrate having similar crystal symmetry. In this framework, the conventional lattice matching epitaxy becomes a special case where a matching of lattice constants or the same planes is involved with a small misfit of less than 7%–8%. In large lattice mismatch systems, we show that epita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

26
392
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 545 publications
(426 citation statements)
references
References 19 publications
26
392
1
Order By: Relevance
“…According to the domain epitaxy paradigm, 15 {110} half-planes match with 16 (À2110) planes of sapphire to accommodate the planar lattice misfit. [34] These results on epitaxial growth are fully consistent with cross-section TEM results, shown in Figure 7(a) for diamond and Figure 15(a) for cBN. Since diamond and cBN are grown from super undercooled liquid, they can be doped with both n-and p-type dopants.…”
Section: R E T R a C T E D A R T I C L Esupporting
confidence: 80%
See 2 more Smart Citations
“…According to the domain epitaxy paradigm, 15 {110} half-planes match with 16 (À2110) planes of sapphire to accommodate the planar lattice misfit. [34] These results on epitaxial growth are fully consistent with cross-section TEM results, shown in Figure 7(a) for diamond and Figure 15(a) for cBN. Since diamond and cBN are grown from super undercooled liquid, they can be doped with both n-and p-type dopants.…”
Section: R E T R a C T E D A R T I C L Esupporting
confidence: 80%
“…By providing a planar matching (0001) sapphire epitaxial template for diamond as well as cBN growth from super undercooled liquid, we have obtained large-area single-crystal thin films through domain matching epitaxy paradigm, where large misfit is accommodated by integral multiple matching of lattice planes across the film/substrate interface. [34] Table III provides a summary of domain matching epitaxy parameters to accommodate large lattice misfit between diamond/sapphire and cBN/sapphire interfaces. [34] Figure 16(a) shows a large-area single-crystal h111i diamond thin film which has grown epitaxially on (0001) sapphire substrate with a following epitaxial relationships: h111i dia // h0001isapphire out of the plane and in-plane h110i diamond // hÀ2110i sapphire.…”
Section: R E T R a C T E D A R T I C L Ementioning
confidence: 99%
See 1 more Smart Citation
“…Previously, the dislocation density at the Co/ FeF 2 interface ͑dislocations help relieve misfit strain between the AF film and substrate͒ 51 was measured with transmission electron microscopy and found to be about half of what would be expected to fully relieve the mismatch between the lattice parameters of FeF 2 and MgF 2 . 32,52,53 Here, we have shown that microstrain is indeed present in the FeF 2 film.…”
Section: Figmentioning
confidence: 99%
“…To understand how this huge lattice mismatch was accommodated between Mg 2 Si and Si, its interfacial structure was investigated. To do this, Fourier-filtered TEM image of the interfacial region 14 was acquired from Fig. 2͑b͒ and the result is shown in Fig.…”
mentioning
confidence: 99%